Integrating Trees and Livestock on Familiy Farms: the Farmer's vision - Tamosiunas, Martha (Agrociencia Uruguay, 2020)
The integration of forestry and livestock was promoted by the Livestock Programme; private forestry companies also made special forest plans to promote it. Both had a limited level of adoption. This research explored the determinants of the decision to include or not trees into livestock plots, for producers with up to 1250 ha CONEAT 100 when they were subjects of forestry promotional activities. The initial sample was 54 small producers, 27 adopters and 27 non adopters, paired by their physical potential. The study consisted of a semi-structured interview schedule focused on the analysis of forestry investment decision. The results indicate that producers with previous silvopastoral experience do afforest because they are convinced of the benefits for the livestock herd. The non-adopters group does not think that the trees are harmful to the rodeo, but they perceive afforestation as an increase in costs and hours of work without immediate benefits. Subsidies and tax benefits are not enough to raise these restrictions. It is concluded that the main reason of non-adoption, is the lack of experience in the management of grazing with shadow. Increasing forestry adoption would require making economically viable the silvopastoral small-scale production, and developing comprehensive management plans together with producers in order to identify trees as a compo-nent with potential to generate revenue for the production unit.